2018
DOI: 10.4187/respcare.06243
|View full text |Cite
|
Sign up to set email alerts
|

A New Formula for Predicting the Fraction of Delivered Oxygen During Low-Flow Oxygen Therapy

Abstract: BACKGROUND: During O 2 therapy at low flow in patients who breathe spontaneously, the fraction of delivered O 2 (F DO 2 ) is unknown. In recent years, F DO 2 prediction formulas have been proposed. However, they do not take into account the effect of inspiratory flow (V I ) on the F DO 2 . The aim of this study was to validate a new F DO 2 prediction formula, which takes into account the V I and compares it with other F DO 2 prediction formulas. METHODS: During a bench study, spontaneous breathing was generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…A key variable in predicting the average inhaled O 2 concentration was the average inhalation flow, a function of inhaled tidal volume (V T ) and inspiratory time. This result echoes the findings of Duprez et al, 25 who also recently concluded that the average inspiratory flow has a major impact on average inhaled O 2 concentration during O 2 delivery at low flow to spontaneously breathing patients.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…A key variable in predicting the average inhaled O 2 concentration was the average inhalation flow, a function of inhaled tidal volume (V T ) and inspiratory time. This result echoes the findings of Duprez et al, 25 who also recently concluded that the average inspiratory flow has a major impact on average inhaled O 2 concentration during O 2 delivery at low flow to spontaneously breathing patients.…”
Section: Introductionsupporting
confidence: 90%
“…This indicates that the tracheal concentration of the delivered gas is strongly influenced by breathing pattern, a result corroborated by similar studies of continuous flow O 2 delivery. 24,25 Reasonably predictive estimates for the average inhaled concentration at the trachea (6 4.5 ppm NO at higher flow, 6 1.8 ppm NO at lower flow) were obtained in this study by accounting for the concentration and flow of the source-gas, as well as V T and inspiratory time of the patient (Equation 2). Measured concentrations tended to be somewhat higher than predicted, except in the sleep case.…”
Section: Discussionmentioning
confidence: 80%
“…formulation is similar to that proposed by Duprez et al . [ 36 ], who also conducted bench experiments to improve prediction of oxygen delivery to adults, and who also observed a major impact of the average inhalation flow rate on delivered oxygen concentrations. A similar set of algebraic equations was also developed earlier in the context of oxygen delivery to infants by Benaron and Benitz [ 10 ], although these authors based the formulation of their equations on inhaled volumes, rather than on average inhaled flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental apparatus was constructed as shown in Figure 1 . Spontaneous breathing was generated with a mechanical ventilator (LTV 1200, CareFusion, San Diego, CA, USA) and two sets of two compartments training and test lung (TTL, Model 5600i, Michigan Instruments, Grand Rapids, Michigan) [ 26 ]. We linked the two TTLs with two rigid metal strap manually for three bellows.…”
Section: Methodsmentioning
confidence: 99%
“…Although the increasing use of continuous monitoring of oxygen saturation by pulse oximetry (SpO 2 ) provides an assessment of the adequacy of oxygenation, the risk may not be recognized since SpO 2 may remain in a satisfactory range because of hyperoxia [ 12 ]. The ideal method for determining the FiO 2 may be to sample tracheal air; however, the invasive procedure has only been performed in small numbers and may lead to changes in patterns [ 26 ].…”
Section: Introductionmentioning
confidence: 99%